A comprehensive methodology for design and development of an integrated microheater for on-chip DNA amplification. (9th May 2018) - Barman, Ujjal; Wiederkehr, Rodrigo Sergio; Fiorini, Paolo; Lagae, Liesbet; Jones, Benjamin
Abstract: This paper presents the design and development of an optimized aluminum microheater integrated onto a biochip for the amplification of DNA using polymerase chain reaction (PCR). A coupled 3D finite element electro-thermal simulation has been used to aid in the design of the microheater and the PCR reactor. The microheater has a special shape, designed to provide a uniform temperature throughout the PCR chamber. The microreactor is fabricated at the center of a 20 mm  ×  20 mm silicon chip. It has a meandered shape, a volume of 1.89 µ l and occupies a square area with a side of 3.8 mm. Microchannels to transport fluid in and out of the reactor are also provided. After heater design optimization, the simulated temperature of the fluid volume within the PCR chamber is very uniform (95% of the volume has a temperature within  ±0.2 °C when the average temperature is 60 °C). This result is validated by DNA melting point experiments, showing a very similar uniformity. A PCR experiment, consisting of 50 cycles of amplification is conducted to demonstrate functionality of the system; amplifications is uniform across the reactor with variation of the threshold cycle within about 0.5 units.